A tool to simplify the management of homogeneous and heterogeneous grids - Aguiar, Cesar S. [UNESP]; Cruz, Daniel I. [UNESP]; Cavenaghi, Marcos A. [UNESP]; Spolon, Roberta [UNESP]; Lobato, Renata S. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2009)
To simplify computer management, several system administrators are adopting advanced techniques to manage software configuration on grids, but the tight coupling between hardware and software makes every PC an individual managed entity, lowering the scalability and increasing the costs to manage hundreds or thousands of PCs. This paper discusses the feasibility of a distributed virtual machine environment, named Flexlab: a new approach for computer management that combines virtualization and distributed system architectures as the basis of a management system. Flexlab is able to extend the coverage of a computer management solution beyond client operating system limitations and also offers a convenient hardware abstraction, decoupling software and hardware, simplifying computer management. The results obtained in this work indicate that FlexLab is able to overcome the limitations imposed by the coupling between software and hardware, simplifying the management of homogeneous and heterogeneous grids. © 2009 IEEE.
Keywords: Distributed system architecture; Distributed virtual machines; Hardware and software; Management systems; New approaches; Operating systems; Software configuration; System administrators; Tight coupling; Virtualizations; Computer architecture; Computer operating systems; Management; Microcomputers; Computer hardware